Social Media-Based Digital Marketing Strategies to Increase Purchasing Decisions: Literature Review - Febrilian Naufal Shafly; Januar Wibowo (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2026)
The rapid growth of digital technology has transformed marketing practices, positioning social media as a major platform for consumer interaction and influencing purchasing decisions. This study aims to examine how social media-based digital marketing strategies contribute to consumer purchasing decisions, with particular attention to the role of entertainment-oriented content. A qualitative library research approach was employed by reviewing approximately drawing on 72 scholarly sources peer-reviewed journal articles, books, conference proceedings, and other relevant academic publications on digital marketing, social media engagement, entertainment marketing, and consumer behavior. The selected literature was analyzed using descriptive and integrative techniques to identify recurring themes, patterns, and relationships among key concepts. The review indicates broad agreement that social media marketing contributes to stronger brand awareness, higher consumer engagement, and greater opportunities for interactive communication. Many studies also suggest that consumer trust functions as an important mechanism linking these outcomes to purchase intentions, although the strength of this relationship varies across contexts and industries. In addition, the literature consistently highlights entertainment oriented content including storytelling, humor, short-form videos, viral campaigns, and live streaming as an effective approach for attracting audience attention, encouraging participation, and strengthening emotional connections with brands. Overall, the findings suggest that successful social media marketing strategies integrate informative content, entertainment value, audience engagement, and personalized communication to improve marketing effectiveness and support consumer purchasing decisions in increasingly competitive digital environments.